PERCEIVED STRESS AND COPING STRATEGIES IN UNIVERSITY ADMINISTRATION AND SERVICES STAFF - Corchuelo, Angelines DÃaz; Herrera, Ramona Rubio; Pozo, Eulogio CordÃ³n (European Scientific Journal, ESJ, 2016)
This study was conducted to explore the stress levels and the coping strategies used by the administration and services staff (PAS) of a scientific and technical campus. This research was carried out among workers of the University of Granada. A total of 352 workers (55.4% woman and 44.6% man), representing 84% of the personal of the campus, completed anonymously questionnaires with regard to perceived stress rates measured by the Perceived Stress Scale (PSS-14 version), and the Stress Coping Questionnaire (CAE). Statistical analysis were performed to establish the relationship between the level of perceived stress and some sociodemographic variables such as age, marital status, number of children, people depending on them, healthy or harmful habits, years in the institution and type of contract, as well as coping strategies used. The results show statistically significant differences in the level of perceived stress in some of the factors discussed, as well as certain relationship between stress levels and certain coping strategies.